2017
DOI: 10.3389/fmicb.2017.01406
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Resistance Genes Identified from Distinct Soil Environments in China by Functional Metagenomics

Abstract: Soil microbiota represents one of the ancient evolutionary origins of antibiotic resistance and has been increasingly recognized as a potentially vast unstudied reservoir of resistance genes with possibilities to exchange with pathogens. Tetracycline resistance is one of the most abundant antibiotic resistances that may transfer among clinical and commensal microorganisms. To investigate tetracycline resistance genes from soil bacteria in different habitats, we performed functional analysis of three metagenomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 37 publications
1
44
0
1
Order By: Relevance
“…However, there were over 800 genes in the B. animalis subsp. lactis genomes, nearly 300 of which were upregulated in the LOG experiments, that were not assigned to a metabolic category, and novel antibiotic resistance genes in bifidobacteria are constantly being identified ( 69 ). Thus, there are many factors yet to be discovered that may also contribute broadly to antibiotic resistance in food and probiotic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were over 800 genes in the B. animalis subsp. lactis genomes, nearly 300 of which were upregulated in the LOG experiments, that were not assigned to a metabolic category, and novel antibiotic resistance genes in bifidobacteria are constantly being identified ( 69 ). Thus, there are many factors yet to be discovered that may also contribute broadly to antibiotic resistance in food and probiotic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…The tetX gene has also been observed in a variety of environmental bacteria, including Myroides odoratimimus ( Ming et al, 2017 ), Sphingobacterium sp. ( Ghosh et al, 2009 , 2014 ), and Flavobacterium psychrophilum ( Duchaud et al, 2018 ), and metagenomic samples including Chinese soil ( Wang et al, 2017 ), human feces ( Ohashi and Fujisawa, 2017 ), and hospital wastewater ( Wang et al, 2018 ). The tetX gene is encountered in a wide range of ecosystems (human gut, soil, hospital wastewater) and is present on mobile genetic elements primed for horizontal gene transfer.…”
Section: Tetracycline Destructasesmentioning
confidence: 99%
“…This coincided with a point of view that lots of ARGs evolved from natively functional genes of the bacterium (Wright, ). Fluoroquinolone is the most used antibiotic in China and the fluoroquinolone resistant genes were prevalent in China (Xu et al, ; Zhang et al, ; Zhang, Lu, Wang, Pang, & Zhao, ), similar situation was found in several relatively abundant resistance types such as β‐lactam and tetracycline (Wang et al, ; ZHANG et al, , ; Zhu et al, ).…”
Section: Discussionmentioning
confidence: 84%